Answer

Verified

447.9k+ views

Hint: To solve this problem, one needs to be aware about the generalised equation of a parabola. This equation is given by ${{\left( \dfrac{px+qy+r}{\sqrt{{{p}^{2}}+{{q}^{2}}}} \right)}^{2}}=4a\left( \dfrac{lx+my+n}{{{l}^{2}}+{{m}^{2}}} \right)$. Here, a is the focus of the parabola. Further; p, q, r, l, m and n are the constants which will one comes across as the equation is solved. We will compare this equation with one given in the problem to trace the parabola to get the value of these constants.

Complete step-by-step answer:

To solve this problem, one must be aware about the general equation of parabola in detail. Generally, one is aware about the equation ${{y}^{2}}=4ax$ where there is no xy term (Here, a is the length of the focus of the parabola). However, in this problem as we expand the terms of the question, there will be a xy term, thus we make use of a different generalised equation. Thus, first to begin with, we expand the terms, we get,

${{(x-4y)}^{2}}=51y$

${{x}^{2}}+16{{y}^{2}}-8xy=51y$

Now, we try to compare with the below equation –

${{\left( \dfrac{px+qy+r}{\sqrt{{{p}^{2}}+{{q}^{2}}}} \right)}^{2}}=4a\left( \dfrac{lx+my+n}{{{l}^{2}}+{{m}^{2}}} \right)$-- (1)

Now, to start solving, we use a small trick, we introduce a variable (in this case k). To explain,

${{(x-4y+k)}^{2}}=51y+2kx-8ky+{{k}^{2}}$

(Thus, to make the equation to compare to (1), we do this manipulation. Also, since, we have added k in the square term on LHS, we have to subsequently add the terms on RHS for equality to hold true.)

${{(x-4y+k)}^{2}}=2kx+(51-8k)y+{{k}^{2}}$ -- (A)

Thus, we have two line equations –

x-4y+k=0 -- (2)

2kx+(51-8k)y+${{k}^{2}}$=0 -- (3)

These lines are perpendicular to each other since these are the equations of the axis and line perpendicular to the axis passing through the vertices of the parabola.

Let slope of (2) be m and slope of (3) be n. Thus,

m=$\dfrac{1}{4}$

n=\[\left( \dfrac{-2k}{51-8k} \right)\]

We have mn=-1 (condition of perpendicular lines)

Thus,

$\Rightarrow$ $\dfrac{1}{4}\times \left( \dfrac{-2k}{51-8k} \right)$=-1

Solving, we get,

$\begin{align}

& -2k=-4(51-8k) \\

& -2k=-204+32k \\

& 34k=204 \\

& k=6 \\

\end{align}$

We put this value in (A), we get,

\[\begin{align}

& {{(x-4y+6)}^{2}}=12x+(51-48)y+36 \\

& {{(x-4y+6)}^{2}}=12x+3y+36 \\

& {{(x-4y+6)}^{2}}=3(4x+y+12) \\

& {{(x-4y+6)}^{2}}=4\times \dfrac{3}{4}\times (4x+y+12) \\

& {{\left( \dfrac{x-4y+6}{\sqrt{17}} \right)}^{2}}=4\times \dfrac{3}{4}\times \dfrac{1}{\sqrt{17}}\times \dfrac{(4x+y+12)}{\sqrt{17}} \\

\end{align}\]

Thus, we can finally compare this to (1)

${{\left( \dfrac{px+qy+r}{\sqrt{{{p}^{2}}+{{q}^{2}}}} \right)}^{2}}=4a\left( \dfrac{lx+my+n}{{{l}^{2}}+{{m}^{2}}} \right)$

We can find, the constants value by comparing,

p=1, q=-4, r=6, a=$\dfrac{3}{4\sqrt{17}}$, l=4, m=1, n=12

To get the vertices, we have to solve the equations

x-4y+6=0 and 4x+y+12=0

Solving, we get,

x=$\dfrac{-54}{17},y=\dfrac{12}{17}$

Thus, the required parabola will have the above vertices with axis as x-4y+6=0. This will look as –

Note: While solving questions related to parabola apart from the familiar equation ${{y}^{2}}=4ax$, we should also be aware of the general equation of the parabola given by ${{\left( \dfrac{px+qy+r}{\sqrt{{{p}^{2}}+{{q}^{2}}}} \right)}^{2}}=4a\left( \dfrac{lx+my+n}{{{l}^{2}}+{{m}^{2}}} \right)$. This equation is especially useful when parabola involves xy terms in its equation.

Complete step-by-step answer:

To solve this problem, one must be aware about the general equation of parabola in detail. Generally, one is aware about the equation ${{y}^{2}}=4ax$ where there is no xy term (Here, a is the length of the focus of the parabola). However, in this problem as we expand the terms of the question, there will be a xy term, thus we make use of a different generalised equation. Thus, first to begin with, we expand the terms, we get,

${{(x-4y)}^{2}}=51y$

${{x}^{2}}+16{{y}^{2}}-8xy=51y$

Now, we try to compare with the below equation –

${{\left( \dfrac{px+qy+r}{\sqrt{{{p}^{2}}+{{q}^{2}}}} \right)}^{2}}=4a\left( \dfrac{lx+my+n}{{{l}^{2}}+{{m}^{2}}} \right)$-- (1)

Now, to start solving, we use a small trick, we introduce a variable (in this case k). To explain,

${{(x-4y+k)}^{2}}=51y+2kx-8ky+{{k}^{2}}$

(Thus, to make the equation to compare to (1), we do this manipulation. Also, since, we have added k in the square term on LHS, we have to subsequently add the terms on RHS for equality to hold true.)

${{(x-4y+k)}^{2}}=2kx+(51-8k)y+{{k}^{2}}$ -- (A)

Thus, we have two line equations –

x-4y+k=0 -- (2)

2kx+(51-8k)y+${{k}^{2}}$=0 -- (3)

These lines are perpendicular to each other since these are the equations of the axis and line perpendicular to the axis passing through the vertices of the parabola.

Let slope of (2) be m and slope of (3) be n. Thus,

m=$\dfrac{1}{4}$

n=\[\left( \dfrac{-2k}{51-8k} \right)\]

We have mn=-1 (condition of perpendicular lines)

Thus,

$\Rightarrow$ $\dfrac{1}{4}\times \left( \dfrac{-2k}{51-8k} \right)$=-1

Solving, we get,

$\begin{align}

& -2k=-4(51-8k) \\

& -2k=-204+32k \\

& 34k=204 \\

& k=6 \\

\end{align}$

We put this value in (A), we get,

\[\begin{align}

& {{(x-4y+6)}^{2}}=12x+(51-48)y+36 \\

& {{(x-4y+6)}^{2}}=12x+3y+36 \\

& {{(x-4y+6)}^{2}}=3(4x+y+12) \\

& {{(x-4y+6)}^{2}}=4\times \dfrac{3}{4}\times (4x+y+12) \\

& {{\left( \dfrac{x-4y+6}{\sqrt{17}} \right)}^{2}}=4\times \dfrac{3}{4}\times \dfrac{1}{\sqrt{17}}\times \dfrac{(4x+y+12)}{\sqrt{17}} \\

\end{align}\]

Thus, we can finally compare this to (1)

${{\left( \dfrac{px+qy+r}{\sqrt{{{p}^{2}}+{{q}^{2}}}} \right)}^{2}}=4a\left( \dfrac{lx+my+n}{{{l}^{2}}+{{m}^{2}}} \right)$

We can find, the constants value by comparing,

p=1, q=-4, r=6, a=$\dfrac{3}{4\sqrt{17}}$, l=4, m=1, n=12

To get the vertices, we have to solve the equations

x-4y+6=0 and 4x+y+12=0

Solving, we get,

x=$\dfrac{-54}{17},y=\dfrac{12}{17}$

Thus, the required parabola will have the above vertices with axis as x-4y+6=0. This will look as –

Note: While solving questions related to parabola apart from the familiar equation ${{y}^{2}}=4ax$, we should also be aware of the general equation of the parabola given by ${{\left( \dfrac{px+qy+r}{\sqrt{{{p}^{2}}+{{q}^{2}}}} \right)}^{2}}=4a\left( \dfrac{lx+my+n}{{{l}^{2}}+{{m}^{2}}} \right)$. This equation is especially useful when parabola involves xy terms in its equation.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Why Are Noble Gases NonReactive class 11 chemistry CBSE

Let X and Y be the sets of all positive divisors of class 11 maths CBSE

Let x and y be 2 real numbers which satisfy the equations class 11 maths CBSE

Let x 4log 2sqrt 9k 1 + 7 and y dfrac132log 2sqrt5 class 11 maths CBSE

Let x22ax+b20 and x22bx+a20 be two equations Then the class 11 maths CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

How many crores make 10 million class 7 maths CBSE

The 3 + 3 times 3 3 + 3 What is the right answer and class 8 maths CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE